Coping with Job Insecurity: Employees with Grit Create I-Deals - Lopez-Bohle, S (American Psychological Association, 2021)
Although job insecurity has been shown to predict numerous adverse outcomes, more is yet to be known about the mechanisms that explain when and why these effects will occur. Using social exchange as our theoretical foundation and three-wave lagged survey data collected from N = 300 employees within the United States, the current study found support for the contention that individuals with greater job insecurity pursue fewer idiosyncratic deals (I-Deals) with their employers. Fewer I-Deals in turn were associated with lower affective commitment, and higher turnover intentions, perceived psychological contract breach, and psychological contract violation. However, these indirect effects were conditional upon employee levels of grit (specifically, perseverance of effort), such that higher grit attenuated the negative relationship between job insecurity and the pursuit of I-Deals. Given that employees often have little control over the source of their experienced job insecurity (e.g., impending layoffs, a poor economy, announced merger or acquisition), these findings hold promise in potentially alleviating the well-documented negative outcomes of job insecurity through interventions designed to increase employee levels of grit and facilitate the creation of I-Deals. © 2021 American Psychological Association